2013
DOI: 10.1016/j.carbpol.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and starch digestibility of Scirpus grossus flour and starch

Abstract: Flour and starch isolated from the tubers of Scirpus grossus were investigated for their physicochemical properties and starch digestibility. The flour was extracted using two different processes namely peeled and unpeeled processes. Proximate analysis revealed that the flours from both processes contain considerably high total starch, more than 80%, which indicate their potential use as starchy foods. The amylose content of the flours and starches ranged from 29 to 32%. Starch granules of S. grossus were oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…A biphasic trend of amylase hydrolysis has also been observed in starches [16]. The starch showed significantly higher hydrolysis by PPA and AAG than flour; this was in agreement with the result of Lerdluksamee et al [38], who reported that Scirpus grossus starch has a higher digestion rate than flour.…”
Section: Degree Of Hydrolysissupporting
confidence: 89%
“…A biphasic trend of amylase hydrolysis has also been observed in starches [16]. The starch showed significantly higher hydrolysis by PPA and AAG than flour; this was in agreement with the result of Lerdluksamee et al [38], who reported that Scirpus grossus starch has a higher digestion rate than flour.…”
Section: Degree Of Hydrolysissupporting
confidence: 89%
“…The in-vitro starch digestibility procedure was adapted from Lerdluksamee et al (2013), Sopade and Gidley (2009) and Chanvrier et al (2007) with slight modification. Briefly, about 0.5 g of grinded samples were weighed in flask (250 ml) and then treated by 1 mL artificial saliva (porcine pancreatic alpha amylase; 250 U; A3176) and 5 ml pepsin (Sigma, P6887-250 M) in 0.02 M HCl (pH 2.0).…”
Section: In-vitro Bread Digestibility Analysismentioning
confidence: 99%
“…e released glucose was measured as the absorbance of the coloration using the UV-spectrophotometer at 510 nm. Total starch (%) was expressed on a dry weight basis [18].…”
Section: Total Starch and Estimated Glycemic Indexmentioning
confidence: 99%
“…Single-point measurement of starch digestion at 90 min (HI90) in the samples was also used to calculate the glycemic index (GI). Hence, using the parameter of the modified first-order kinetic model for both the rice sample and white bread (reference), the average GI (GI avg ) for each sample was calculated using the following equation [18]:…”
Section: Total Starch and Estimated Glycemic Indexmentioning
confidence: 99%